2004
DOI: 10.1071/sr03029
|View full text |Cite
|
Sign up to set email alerts
|

Wettability of soil aggregates from cultivated and uncultivated Ustolls and Usterts

Abstract: Soil organic matter can modify the interaction of clay minerals with water, limiting the rate of water intake of swelling clays and stabilising soil aggregates. Soil structural stability and organic C content usually decrease with cultivation. Faster wetting increases stresses on aggregates and decreases stability. Aggregate wettabilities of prairie soils under 3 different management systems (grassland, no-till, and conventional-till) were compared in the Northern Great Plains of the USA. Six Ustolls and 2 Ust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 33 publications
0
23
1
Order By: Relevance
“…The significant development of water repellency due to adoption of no-till technology observed in the 8 soils contrasts with some previous studies reporting no differences in water repellency between no-till and plow tillage (Eynard et al, 2004) but agrees with others which reported slower aggregate wetting in no-till soil (Chan, 1992;Hallett et al, 2001;Blanco-Canqui et al, 2007). These inconsistencies in data suggest the site-specificity of no-till impacts.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The significant development of water repellency due to adoption of no-till technology observed in the 8 soils contrasts with some previous studies reporting no differences in water repellency between no-till and plow tillage (Eynard et al, 2004) but agrees with others which reported slower aggregate wetting in no-till soil (Chan, 1992;Hallett et al, 2001;Blanco-Canqui et al, 2007). These inconsistencies in data suggest the site-specificity of no-till impacts.…”
Section: Discussioncontrasting
confidence: 54%
“…A watershed study by Blanco-Canqui et al (2007) showed that soils under 44-yr NT continuous corn had WDPT about twice higher than plowed soils on a sloping silt loam. In contrast, a field study by Eynard et al (2004) showed no significant differences in WR between NT and PT fields across loam, silt loam, silty clay loam, silty clay, and clay soils.…”
Section: Introductionmentioning
confidence: 60%
“…The results generally may be attributed to the organic carbon content of the textures as water stability of micro aggregates depend on OC binding agents a characteristics of soil independent of the land use management and the extent of tillage. Denef et al 2001 andEynard et al 2004 observed that the structural stability of aggregates decrease with OC content and cultivation. Soil structure and aggregates according to Holeplass et al 2004 andKhurshid et al 2006 are strongly influenced by cultivation related practices.…”
Section: Physical and Chemical Properties Of The Soils Used For The Smentioning
confidence: 99%
“…Soil water repellency (SWR) has serious effects on natural ecosystems, like preferential flow, irregular pattern of vegetation growth, enhanced surface runoff and soil erosion (Burcar et al, 1994;DeBano, 1981;Ehwald et al, 1961;Imeson et al, 1992;Shakesby et al, 1993) and it is common especially in uncultivated sandy soils (Blanco-Canqui, 2011;Dekker, 1998) although different observations are also reported for instance from olive orchards (Bughici and Wallach, 2016) or from prairie soils (Eynard et al, 2004). Water repellency phenomenon results from the decrease in attraction between soil particles and water molecules which means that large-scale environmental effects may depend on processes that vary at microscopic scales.…”
Section: Introductionmentioning
confidence: 99%